2016
DOI: 10.1016/j.eurpolymj.2016.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-based ionic liquid type dependence of the bending response of polymer actuators

Abstract: Actuators based on polymer blends of poly(vinylidene fluoride) (PVDF) with 40 % of different ionic liquids (IL) are prepared by solvent casting. NTf2] were selected in order to evaluate the effect of anion and cation sizes in the bending properties. The microstructure, mechanical and electrical properties of the blend depend on the IL type, which in turn leads to a different bending response. In particular, the mechanical properties are independent on the IL type but the AC conductivity of the composites depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 32 publications
0
69
0
Order By: Relevance
“…[ 49 ] Thus, actuators based on PVDF and ILs with different anions, [HMIM][Cl] and [HMIM][TFSI] have been developed to study the effect of anion size and filler content on the bending response. [ 50 ] It was observed that the polymer crystallizes in the electroactive β‐phase in the presence of the ILs, regardless of the nature and content of the IL. Moreover, the size of the polymer spherulites decreases with increasing IL concentration and with the incorporation of anions of larger size ( Figure ).…”
Section: Ionic Liquid‐based Polymer Composites and Their Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 49 ] Thus, actuators based on PVDF and ILs with different anions, [HMIM][Cl] and [HMIM][TFSI] have been developed to study the effect of anion size and filler content on the bending response. [ 50 ] It was observed that the polymer crystallizes in the electroactive β‐phase in the presence of the ILs, regardless of the nature and content of the IL. Moreover, the size of the polymer spherulites decreases with increasing IL concentration and with the incorporation of anions of larger size ( Figure ).…”
Section: Ionic Liquid‐based Polymer Composites and Their Applicationsmentioning
confidence: 99%
“…Different imidazolium‐based ILs were also incorporated into a PVDF matrix to study the effect of the alkyl chain length of the cation ([EMIM] + , [HMIM] + , and [C 10 MIM] + ), and the anion ([TFSI] − and [Cl] − ) on the mechanical and electrical properties of the composites. [ 50 ] The mechanical properties are nearly independent of the IL type, whereas the conductivity is more related to the anion type than to the size of the alkyl chain. The maximum bending response (0.3%) was obtained for the IL [EMIM][TFSI] ( Figure ).…”
Section: Ionic Liquid‐based Polymer Composites and Their Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows the results of dielectric constants of the prepared PVC gels as a function of input frequency. The dielectric constants are increased in the low-frequency range (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It can be considered that, in a nonionic PVC gel physically crosslinked with plasticizer, DBA molecules are charged and polarized under the electric field, and then the polarized DBA easily facilitates the free dipole reorientation of the PVC chain in the PVC gel network [28].…”
Section: Resultsmentioning
confidence: 99%
“…I. Chilibon et al introduced a bending actuator using prepolarized piezoelectric bimorph structure consisting of two PVDF thin films [17]. R. Mejri et al proposed a new method to fabricate a high-performance bending actuator using an ionic liquid/PVDF blend [18]. Babita Gaihre et al synthesized a PPy-PVDF multilayered electroactive polymer and fabricated a bending actuator using the PPy-PVDF multilayered polymer [19].…”
Section: Introductionmentioning
confidence: 99%